Coronary heart disease and arterial hypertension prevalence dynamics in Tumen female population: five-year monitoring - E. V. Akimova (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To study prevalence dynamics for coronary heart disease (CHD), systolic and diastolic arterial hypertension (SAH, DAH) in middle-aged Tumen women, according to the two cardiology screening data. Material and methods. Based on electorate lists of one Tumen City administrative district, two representative samples were formed, with a five-year interval: 1000 females aged 25-64 years (response rate 81,3%) and 500 females aged 35-54 years (response rate 78,6%). Results. CHD prevalence in open Tumen city female population was 13,2%. During fiveyear monitoring period, CHD prevalence had increased, due to “possible” forms, increased isolated SAH and decreased DAH rates in 45-54-year-olds. Conclusion. Population health changes over time, linked to socioeconomical, ecological, and behavioral factors, are to be addressed with time- and population-specific, epidemiologically based preventive measures.